Smart Book for Fun Mathematics Learning: Buku Cerdas untuk Pembelajaran Matematika yang Menyenangkan - Murtiani; Nisak, Nur Maslikhatun (Indonesian Journal of Education Methods Development, 2025)
General background: Early mathematics learning plays a crucial role in shaping children’s cognitive development, yet conventional methods often fail to sustain young learners’ interest. Specific background: Children aged 4 to 7 years commonly struggle with maintaining focus when introduced to abstract mathematical concepts such as addition and subtraction. Knowledge gap: Existing teaching materials often lack interactive features that simultaneously support conceptual understanding and engagement in early mathematics learning. Aims: This study introduces the Fun Learning Mathematics Smart Book, designed to facilitate enjoyable and effective mathematics learning for early grade students. Results: The smart book, consisting of 30 colorful and interactive pages, integrates number recognition, counting concrete objects, coloring, matching, and solving story-based problems while embedding elements of play and learning. It was found to keep children motivated, reduce boredom, and stimulate both hemispheres of the brain during mathematics activities. Novelty: Unlike conventional textbooks, this smart book combines cognitive training with fine motor skill development through playful activities tailored to early learners. Implications: The findings suggest that this learning medium can serve as an innovative approach for educators and parents to support foundational mathematics learning in a way that is both engaging and developmentally appropriate.Highlights: Smart Book supports fun mathematics learning for young children. Activities include counting, coloring, matching, and story problems. Helps train both cognitive skills and fine motor development. Keywords: Smart Book, Mathematics, Addition, Subtraction, Early Childhood